Catalyst-Free Periodate Activation by Solar Irradiation for Bacterial Disinfection: Performance and Mechanisms - Fuyang Liu; Li, Zhengmao; Qiqi Dong; Chenyi Nie; Wang, Shuai; Boaiqi Zhang; Peng Han; Meiping Tong (Environmental Science and Technology, 2022)
Periodate (PI)-based advanced oxidation process has recently attracted great attention in the water treatment processes. In this study, solar irradiation was used for PI activation to disinfect waterborne bacteria. The PI/solar irradiation system could inactivate Escherichia coli below the limit of detection (LOD, 10 CFU mL–1) with initial concentrations of 1 × 106, 1 × 107, and 1 × 108 CFU mL–1 within 20, 40, and 100 min, respectively. •O2– and •OH radicals contributed to the bacterial disinfection. These reactive radicals could attack and penetrate the cell membrane, thereby increasing the amount of intracellular reactive oxygen species and destroying the intracellular defense system. The damage of the cell membrane caused the leakage of intracellular K+ and DNA (that could be eventually degraded). Excellent bacterial disinfection performance in PI/solar irradiation systems was achieved in a wide range of solution pH (3–9), with coexisting humic acid (0.1–10 mg L–1) and broad solution ionic strengths (15–600 mM). The PI/solar irradiation system could also efficiently inactivate Gram-positive Bacillus subtilis. Moreover, PI activated by natural sunlight irradiation could inactivate 1 × 107 CFU mL–1 viable E. coli below the LOD in the river and sea waters with a working volume of 1 L in 40 and 50 min, respectively. Clearly, the PI/solar system could be potentially applied to disinfect bacteria in water.